Surfactant‐free and controllable synthesis of hierarchically lithiated MoO3 microspheres. (29th December 2020) - Shi, Jiayuan; Zhang, Hongmei; Chen, Xiaotao; Shi, Bin
Abstract: The hierarchically lithiated MoO3 microspheres composed of primary crystallized particles have been prepared in the absence of surfactant. The surface morphologies of the lithiated MoO3 structures can be well regulated through adjusting the adding amounts of ethanol during their synthetic process. The results of XRD patterns and the elemental analysis indicated the decrease of lithium content with the increase of ethanol feeding amount. The obtained lithiated MoO3 samples showed the initial capacities of nearly 300 mAh/g at 30 mA/g and 41.8 mAh/g at 200 mA/g. Therefore, this work has showed a facile way to fabricate the lithiated MoO3 cathode materials with controllable surface morphology and lithium content.